Andronikos Kallistos: A Byzantine Scholar and His Manuscripts in Italian Humanism - Orlandi, Luigi (Studies in Manuscript Cultures, 2023)
Andronikos Kallistos, a leading personality among the Greeks who participated in Italian Humanism, was a scholar, teacher and copyist of manuscripts. This book investigates Kallistos' scholarly and scribal activity by adopting a synergistic approach to historical, philological, codicological and paleographic data, in order to shed light on his role at the time of the transfer of Greek cultural heritage to Italy and, hence, throughout Europe.